2006
DOI: 10.1118/1.2208916
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo based IMRT dose verification using MLC log files and R/V outputs

Abstract: Conventional IMRT dose verification using film and ion chamber measurements is useful but limited with respect to the actual dose distribution received by the patient. The Monte Carlo simulation has been introduced as an independent dose verification tool for IMRT using the patient CT data and MLC leaf sequence files, which validates the dose calculation accuracy but not the plan delivery accuracy. In this work, we propose a Monte Carlo based IMRT dose verification method that reconstructs the patient dose dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 22 publications
2
82
1
Order By: Relevance
“…It was reported that log file analysis should not be solely relied upon for QA as it does not detect systematic machine errors resulting from incomplete calibration [8] [12]. Nevertheless, the log file-based patient-specific QA is advantageous because the QA procedure is less time consuming without phantom positioning errors.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that log file analysis should not be solely relied upon for QA as it does not detect systematic machine errors resulting from incomplete calibration [8] [12]. Nevertheless, the log file-based patient-specific QA is advantageous because the QA procedure is less time consuming without phantom positioning errors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of MLC and backup diaphragm errors for dynamic IMRT, Parsai et al 33 indicated that when MLCs or backup diaphragms alone were perturbed, random errors of at least σ = 1.5 mm were required to cause dose discrepancies greater than 5%, while systematic errors on the order of ±0.5 mm were shown to result in significant dosimetric deviations. In a study that proposed a Monte Carlo based IMRT dose verification method, Luo et al 34 found that an average MLC leaf positional error of 0.2 mm can result in a target dose error of about 1.0%. Mu et al 35 studied the impact of random and systematic MLC leaf position errors for head and neck IMRT patients.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have also stated that DynaLog files have limitations due to the inherent finite precision false(±0.01cmfalse) and different sampling compared to sampling of the dva file planned for the delivered field. Luo et al (19) pointed out the potential inaccuracies of the DynaLog files if the encoders are miscalibrated. The MLC controller records the position of each leaf as MLC motor counts and a conversion factor is then used to convert motor counts to leaf positional information.…”
Section: Discussionmentioning
confidence: 99%